Characteristic Description of Emesis Gravidarum Case to Pregnant Woman in 1st Trimester - Ni Ketut Citrawati; I dewa Putu Arwidiana (GLOBAL HEALTH SCIENCE GROUP, 2023)
There are various changes in body systems during pregnancy. One of the physiological changes that occur in early pregnancy occurs in the gastrointestinal system, namely nausea and vomiting. This disturbing condition is often called emesis gravidarum. Emesis gravidarum is a common occurrence in the first trimester of pregnancy with a prevalence of 50-80% in Indonesia, including 60-80% in primigravida and 40-60% in multigravida. The purpose of this study was to describe the characteristics of emesis gravidarum in first trimester pregnant women at Puskesmas III North Denpasar. This type of research is descriptive research with a quantitative approach. The population in this study were all pregnant women in the first trimester who visited the Puskesmas III North Denpasar area who experienced emesis gravidarum with a population d of 30 people. The results showed that the characteristics of pregnant women in the first trimester who experienced emesis gravidarum were the most dominant, namely characteristics based on gestational age. The characteristics of the majority of pregnant women who experience emesis gravidarum based on age, namely maternal age 26-35 years, based on gestational age, namely 9-12 weeks of gestation, based on parity, namely 1 time, based on education, namely high school, based on occupation, namely private employees, based on aromatherapy information ginger ie never. The conclusion of this study is that the characteristics of first trimester pregnant women who experience emesis gravidarum are in the age category 26-35 years, gestational age 9-12 weeks, parity 1 time, high school education, private work, have never received information on ginger aroma therapy.